2009
DOI: 10.1097/ccm.0b013e31819c1933
|View full text |Cite
|
Sign up to set email alerts
|

Continuous hypertonic saline therapy and the occurrence of complications in neurocritically ill patients*

Abstract: CHS therapy was not associated with an increased rate of infection, deep vein thrombosis, or renal failure. However, there was a significant risk of developing hypernatremia. We conclude that CHS administration in patients with severe injuries is safe as long as sodium levels are carefully monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 60 publications
2
90
0
7
Order By: Relevance
“…26,38 However, although the use of continuous HTS infusion has been shown in adults to be safe, its benefit in ICP reduction has not been demonstrated. 14,39,41,52 We examined HTS therapy using bolus dosing. Therefore, the conclusions can be applied for the use of HTS bolus therapy only and not for the use of continuous HTS infusions to reduce ICP.…”
Section: Dosing Methods: Bolus Versus Continuous Infusionmentioning
confidence: 99%
“…26,38 However, although the use of continuous HTS infusion has been shown in adults to be safe, its benefit in ICP reduction has not been demonstrated. 14,39,41,52 We examined HTS therapy using bolus dosing. Therefore, the conclusions can be applied for the use of HTS bolus therapy only and not for the use of continuous HTS infusions to reduce ICP.…”
Section: Dosing Methods: Bolus Versus Continuous Infusionmentioning
confidence: 99%
“…32 Hypernatremia has itself been associated with elevated creatinine 33 and increased mortality 19,[34][35][36] in patients with brain injury. In 4,296 patients admitted to a neurocritical care unit (only 17% patients had a TBI), results of a retrospective cohort study showed that a Na level [ 160 mEqÁL -1 was independently associated with an increased ICU mortality (odds ratio [OR], 4.8; 95% CI, 2.4 to 9.6).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] One treatment with hypertonic saline often used is a continuous intravenous infusion of 3% sodium chloride solution. 4 However, few studies have evaluated the safety of this treatment in neurocritical care patients. 4 Complications such as hypernatremia, hyperchloremic acidosis, and hypokalemia have been reported.…”
mentioning
confidence: 99%